The Tradition of Humanistic Consciousness in Marxian Materialism - Wang, Zheng (Mediterranean Journal of Social Sciences, 2022)
Traditionally, the researchers of Marx ignored the Epicurean roots for the maturation of Marxian thoughts, insisting that Marx was engaged in it only during his writing of the doctoral dissertation of 1841. Indeed, Epicurus played a decisive role in Marxâ€™s subsequent works, although this reality is not explicitly mentioned. Epicurean atomism, through the theory of the declination of the atom, refers to a utilitarian consciousness for realizing human freedom and ethics. From the heretical tradition of humanism, Marx inherited Epicurean materialism as an important source of the â€œmaterialism of freedomâ€, a materialism that may be considered as a philosophy of emancipation. Besides the freedom of nature from which it ultimately derives, this Marxian idea also combines with that of Epicurus in terms of history: Marxian historiography is actually narrating history in the present, by which we can recall our lack of humanity. Received: 21 September 2021 / Accepted: 24 February 2022 / Published: 5 March 2022